2011
DOI: 10.1118/1.3656683
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of air‐kerma strength determinations for HDR 192Ir sources

Abstract: Purpose: To perform a comparison of the interim air-kerma strength standard for high dose rate (HDR) 192 Ir brachytherapy sources maintained by the University of Wisconsin Accredited Dosimetry Calibration Laboratory (UWADCL) with measurements of the various source models using modified techniques from the literature. The current interim standard was established by Goetsch et al. in 1991 and has remained unchanged to date. Methods: The improved, laser-aligned seven-distance apparatus of the University of W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(64 citation statements)
references
References 29 publications
1
63
0
Order By: Relevance
“…The AKS measured with this technique was used to establish the calibration factor for reference well chambers at UWADCL. [910] The well-type ionization chambers are used in general to determine the AKS in the clinical environment to achieve greater precision due to reproducible geometry. As the detection volume of the well-type ionization chamber is large, it produces high ionization current that can be measured with high precision.…”
Section: Introductionmentioning
confidence: 99%
“…The AKS measured with this technique was used to establish the calibration factor for reference well chambers at UWADCL. [910] The well-type ionization chambers are used in general to determine the AKS in the clinical environment to achieve greater precision due to reproducible geometry. As the detection volume of the well-type ionization chamber is large, it produces high ionization current that can be measured with high precision.…”
Section: Introductionmentioning
confidence: 99%
“…[2] In addition, the primary values of air kerma for the UW250-M beam and the 137 Cs beam were changed by NIST (and other primary laboratories). Rasmussen determined the calibration coefficient for a flat energy response chamber using…”
Section: Calibration Of the Hdr 192 Ir Sourcementioning
confidence: 99%
“…This source has been in use for over 25 years and was first calibrated at the University of Wisconsin -Madison. [4] The latest summary of the calibration of this source is given by Rasmussen, et al [2] The weighted average energy of this source is 397 keV. [4] The output quantity for this source is air kerma strength (AKS) or reference air kerma rate (RAKR); both quantities are the same at 1 m. The air kerma strength is expressed in vacuum at a distance, generally 1 cm.…”
Section: Introductionmentioning
confidence: 99%
“…The overall uncertainty of the measurement was determined by performing an uncertainty budget. Rasmussen et al [6] compared the interim air-kerma strength standard established by Goetsch et al [4] for HDR 192 Ir brachytherapy sources with measurements of the various source models using modified techniques from the literature. They found the differences between the source models to be statistically significant but confirmed that it is not necessary to update the current interim standard of seven distance method.…”
Section: Introductionmentioning
confidence: 99%
“…The in-air measurement of source strength using cylindrical ionization chamber requires the determination of scatter radiation from walls and floor of the room and also the offset in positioning of the chamber. Few studies [4][5][6][7][8][9][10] have been reported for determining the room scatter contribution from an 192 Ir HDR brachytherapy source. Goestch et al [4] described a method for calibrating 192 Ir HDR brachytherapy afterloading systems.…”
Section: Introductionmentioning
confidence: 99%